Dominant Language Acquisition in Destination Countries: Structure, Agency and Reflexivity. (October 2019) - Netto, Gina; Hudson, Maria; Kamenou-Aigbekaen, Nicolina; Sosenko, Filip
This article advances understanding of the structural and agentic factors which influence how migrants in low-paid work reflexively acquire the dominant language of destination countries. Bourdieu's theories on the symbolic power of language and habitus, and theories of reflexivity by Archer and others underpin our analysis of how migrants acquire English in the UK. Analysis of data generated from in-depth qualitative interviews with 31 migrants from EU and non-EU countries in low-paid work reveals that the agency of migrants in increasing proficiency in the language is shaped by access to resources, conscious and unconscious reflexive processes, aspects of embodiment and perceptions of identity by the self and others. We argue that closer attention to the social, political and economic context in which migrants acquire the dominant language of destination countries is needed, as well as greater awareness of the multi-dimensional nature of reflexivity and the constraints on agency.